Delimitação e uso das áreas de contribuição hidrológica por drenagem pluvial ao longo do rio Lonqueador no perímetro urbano de Francisco Beltrão – PR - Lira, Wesley Rodrigues de (2024)
In the southwestern region of the state of Paraná is located the municipality of Francisco Beltrão, which in recent years has been growing gradually. With the increase in buildings along the watersheds in the urban perimeter, some imbalances in the municipal infrastructure are beginning to emerge. With the advance of constructions along the rivers that cut through the city, the Lonqueador River stands out, which is currently channeled in the urban perimeter, with this, possible releases of domestic and industrial effluents may be directed to the river. The Lonqueador River rises in the territory of the neighboring city called Marmeleiro, its natural course continues to run from the south to the north of its Hydrographic Basin, cutting through the neighborhoods: Água Branca, São Cristóvão, Industrial, Vila Nova, Miniguaçu, Presidente Kennedy and the city center, with its mouth in the Marrecas River. With topographic studies and georeferencing, this work aims to delimit the areas of hydrological contribution of the rainwater drainage system of an urban stretch of the Lonqueador river basin, in the municipality of Francisco Beltrão, Paraná, associating the rainfall release points along the main channel of the river and relating it to land use. With georeferencing, mapping of the polygons of rainfall influence and results of the physicochemical analysis of the releases of the urban drainage system, possible points of discharge of domestic and industrial effluents were located.